A pragmatic randomized controlled trial to compare a novel group physiotherapy programme with a standard group exercise programme for managing chronic low back pain in primary care. (1st October 2016) - Daulat, Alex
Abstract : Objectives : To compare a novel group physiotherapy exercise programme with a standard programme for managing chronic low back pain (CLBP) in primary care. Introduction : Group exercise programmes used in physiotherapy practice are a cost effective treatment for managing CLBP but currently lack a combination of individualized specific exercises, one-to-one education and manual therapy. A novel group exercise programme was designed to address these limitations. Methods : The novel group exercise programme (Group A) was compared to a standard group exercise programme used in clinical practice (Group B) in a pragmatic randomized controlled trial with focus groups. Participants with CLBP were allocated to the two programme groups by block randomization. Participants in both groups attended six one-hour programme sessions over a 3-month period. Outcomes measuring function (Functional Rating Index (FRI)), pain (Numerical Pain Rating Scale (NPRS)), quality of life (EQ-5D) and satisfaction with treatment were used to evaluate the effectiveness of the programmes pre- and post-programme attendance and at 6 months. Focus groups were used to explore patients' experiences regarding their treatment in the two group programmes. Results : Eighty-one participants were randomized to the two groups (41 in Group A; 40 in Group B). Both groups showed improvements to function, quality of life, and pain post treatment. There were no significant between-group differences in any outcomes post treatment and small effect sizes were found. Quality of life deteriorated in Group B at 6 months but continued to improve in the novel group. The within group analysis revealed significantly lower FRI and NPRS scores post-programme compared to pre-programme in both groups but these improvements were greater in the novel programme. EQ-5D scores were significantly higher in the novel programme post treatment but not in Group B. The focus group interviews showed that these group programmes provide social support but participants would like further guidance post treatment. Patients prefer individualized exercises as well as one-to-one education which are components of the novel programme. Conclusion : This novel programme may provide a suitable addition to existing programmes available for managing CLBP. It is recommended that this programme be further evaluated in clinical practice.